Political sagacity in the fictional world of Yejide Kilanko’s daughters who walk this path / Shamaila Dodhy - Dodhy, Shamaila (Universiti Teknologi MARA, Negeri Sembilan, 2017)
A literary discourse can recognize history and culture using the canvas of fictive world. For a writer, fiction becomes an ideological screen on which the preceding and contemporaneous issues can be conveniently represented. Contemporary Nigeria is struggling with colonial legacy, identity politics, cultural conflicts and power struggle. This research attempts to examine political thought in Kilanko’s fictional world through an episode of past elections in Nigeria where violence has become a part of political culture since independence. Kilanko depicts corruption, violence, deception, nepotism, on the part of politicians who are enjoying absolute power supported by equally corrupt bureaucratic structure. It gives Kilanko an opportunity to write on the behalf of the suffering nationals who are confronting repressive leadership. By revealing the picture of dystopian Nigerian society, the writer has offered critical assessment of the existing political situation to redirect the actions, beliefs and values observed by her fellow citizens. She has documented historical realities and mysteries which otherwise remain hidden from the descendants.